APLIKASI E-ULOS DENGAN KONSEP CUSTOMER RELATIONSHIP MANAGEMENT UNTUK MEMBANGUN LOYALITAS PELANGGAN - Indra Kelana Jaya; Harlen Gilbert Simanullang; Asaziduhu Gea (STMIK KAPUTAMA, 2020)
Bataknese (such as Batak Toba, Karo, Simalungun, Pakpak) in their ceremonial events (birth, marriage, death) are use of Ulos. Gallery Ulos Sianipar is a business unit selling various Batak weaving such as Ulos, Songket, Kebaya and Batak Traditional Clothing. Gallery Ulos Sianipar use minimum Information Technology in business activities. Analysis SWOT (Strength, Weakness, Opportunities, Threat) aims to capture the organization's needs for system development. IDIC Model (Identify, Differentiate, Interact, Customize) aim to implement the concept of customer relationship management to increase the loyalty of customers